Analysis of the Influence of Work-Life Balance, Work Stress, and Job Satisfaction When Working from Home on the Implementation of Permanent Telework Culture in Legal Business - Anthony Leonard Limanta; Y. Johny Natu Prihanto; Ringkar Situmorang (Profesional Muda Cendekia Publishing, 2023)
This study aims to investigate whether the Work from Home work culture due to the Covid-19 pandemic can be continued and become a new way of working by investigating several potential factors between the phenomena that occur, specifically Work Stress and Work-Life Balance that experienced by employees during Work from Home and Job Satisfaction to make Work from Home work culture becomes permanent, using quantitative research using survey method of 96 legal employee respondents who using Work from Home work methods and works in Jabodetabek office’s location. The findings show that Work from Home has a significant positive effect on Work-Life Balance, Job Satisfaction, and Permanent Telework, and a significant negative effect on Work Stress. Work-Life Balance insignificant effect on Job Satisfaction, Work Stress has a significant negative effect on Job Satisfaction and Job Satisfaction insignificant effect on Permanent Telework, some of the findings are not significantly influenced by the level of employee satisfaction which does not influence enough and also work control issues that need to be solved in management so that workload becomes more measurable also regular meetings are needed to convey problems and evaluate work and also adopt a tasklist application system.